OCA Oracle Database 12c : installation and administration exam guide : (exam 1Z0-062) - Watson, John (Mc Graw Hill, 2014)
This authoritative resource helps you pass the OCA Oracle Database 12c Installation and Administration exam and also serves as an essential, on-the-job reference. Get complete coverage of all OCA objectives for exam 1Z0-062, including: installing and upgrading Oracle Database software; managing the database instance; configuring the Oracle network environment; managing database storage structures; administering user security; managing undo data and data concurrency; implementing Oracle Database auditing; performing database maintenance; managing performance and tuning SQL; managing resources using Oracle Database Resource Manager; automating tasks; moving data; performing backup and recovery; installing Oracle Grid Infrastructure for a standalone server. --